2007
DOI: 10.1002/jso.20824
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in malignant pancreatic neuroendocrine tumors

Abstract: Patients with malignant pancreatic neuroendocrine tumors commonly present with advanced disease. Although, curative resection is not frequent, survival benefit may be obtainable with aggressive surgical management even in the face of metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 27 publications
0
54
0
1
Order By: Relevance
“…The overall survival data did not differ significantly in the two studies (56,58), whereas the third study (57) did not report data on overall survival. Nevertheless, the 5-year survival rate seemed generally higher in patients who had their primary tumor resected, with a difference of 30% in one study, of 33% in a second (57), and no difference in a third study (56). Given the absence of randomization in the examined studies, a bias toward a more aggressive approach in patients with a better overall performance status, a less advanced disease, or possibly with location of the tumor in the body or tail of the pancreas seems likely.…”
Section: Surgery Of Primary Tumormentioning
confidence: 81%
See 1 more Smart Citation
“…The overall survival data did not differ significantly in the two studies (56,58), whereas the third study (57) did not report data on overall survival. Nevertheless, the 5-year survival rate seemed generally higher in patients who had their primary tumor resected, with a difference of 30% in one study, of 33% in a second (57), and no difference in a third study (56). Given the absence of randomization in the examined studies, a bias toward a more aggressive approach in patients with a better overall performance status, a less advanced disease, or possibly with location of the tumor in the body or tail of the pancreas seems likely.…”
Section: Surgery Of Primary Tumormentioning
confidence: 81%
“…Indeed, while ENETS suggests the removal of the primary tumor to make the only persisting problem for intestinal NETs (30), the resection of the primary tumor in metastatic pancreatic NETs is not recommended, except for selected low-risk patients with life-threatening symptoms due to complications (5 (56,57,58), one prospective study with a relatively small sample size and an other two retrospective studies. The overall survival data did not differ significantly in the two studies (56,58), whereas the third study (57) did not report data on overall survival. Nevertheless, the 5-year survival rate seemed generally higher in patients who had their primary tumor resected, with a difference of 30% in one study, of 33% in a second (57), and no difference in a third study (56).…”
Section: Surgery Of Primary Tumormentioning
confidence: 99%
“…Of the 4 studies potentially appropriate to be included in the review [11,15,16,17], 3 were excluded because they did not contain sufficient data for the two treatment arms [11,16,17]. Two additional studies were found by hand searching/search of references of the identified papers [18,19], leaving 3 studies with usable information, by outcome, analysed in detail [15,18,19]. Agreement for these studies was 100% among the two reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…28.3-77% of patients with PNET develop liver metastasis during the course of their disease (36,37). In managing NET with liver metastasis, surgery helps in reducing tumor burden and hormonal secretion in functioning tumor (38,39). If liver metastasis is left untreated, 5-year survival was only 30-40% (40,41).…”
Section: Management With Liver Metastasismentioning
confidence: 99%